DNA binding effects of 2, 2′-bipyridine and 1, 10-phenanthroline ligands synthesized with benzimidazole copper (II) complexes: Crystal structure, molecular docking, DNA binding and anti-cancer studies. (15th July 2022) - Ünver, Hakan; Berber, Burak; Kanat, Beyza; Arafat, Mahmoud; Koparal, Ayse Tansu; Doluca, Osman
Graphical abstract: Highlights: The preliminary data we obtained in the molecular docking study and the similar results of DNA binding with spectroscopic analysis and anti-cancer effect reveal the importance of our study. In our study, the difference in effect of 1, 10-phenanthroline and 2, 2′-bipydrine ligands on the benzimidazole-derived copper complex was clearly demonstrated. DAPI staining was performed to indicate the effect of the complexes on cell nuclei and their effects at different doses were shown. In addition, drug possibilities of the complexes were discussed by analyzing their in silico pharmacokinetic properties. Abstract: Two new copper(II) complexes, [Cu(benzim)2 (bipy)(MeOH)](ClO4 )2 (Complex 1) and Cu(benzim)2 (phen)(MeOH)](ClO4 )2 (Complex 2)] (bipy = 2, 2′-bipyridine, phen = 1, 10-phenanthroline and benzim = 1-benzyl-1H-benzimidazole) have been synthesized and successfully characterized with single crystal x-ray diffraction analysis. Crystal structures of complexes revealed that both possess distorted square pyramidal geometries coordinated with a solvent molecule (CH3 OH) at apical positions. The in vitro cytotoxicity of these Cu(II) complexes was carried out in HCC1428 and HUVEC cell lines. Molecular docking was also used to evaluate and understand the interaction modes of the complexes with the molecular target DNA and HSA (Human Serum Albumin). DNA binding capacities of complexes were analyzed by fluorescent titration method. Structural changes in the nucleus as a result of the effects of the complexes were discussed by viewing them with DAPI staining. Furthermore, biological activities of complexes and ligands were analyzed in silico . The cell lines IC50 results were obtained at similar rates (∼8-fold) to the constant inhibition values obtained by docking studies. In addition, the fluorescence titration and circular dichrosim studies of the compounds with dsDNA-TO complexes showed results in agreement with docking studies. In our study, it was determined that phen ligand has a much more effective biological activity than bipy ligand in copper(II) complex synthesized with benzimidazole.